The impact of COVID-19 uncertainties on energy market volatility: Evidence from the US markets - Mohammad Abedin (Economic Analysis and Policy, 2024)
This research investigates the influence of the COVID-19 on the returns of energy indexes in the US using daily time series data of WTI and Brent markets for the January 2020 – March 2022 period. The findings reveal compelling evidence of the COVID-19 impacting the volatility of energy commodity indexes in the US. Nevertheless, the magnitude of this impact varies across different volatility regimes. Notably, the WTI crude oil exhibits more substantial effects during periods of lower volatility characterised by fewer COVID-19 cases, potentially attributed to market control measures. In contrast, the Brent crude oil displays a more pronounced impact of the COVID-19 during turbulent periods, attributed to the market's openness and the prevalence of speculative participants. The study suggests that participants in the Brent market, driven by a desire to capitalise on price differentials, intensify their activities during turbulent periods, contributing to increased volatility during successive waves of high COVID-19 cases. The observed structural differences between the WTI and Brent commodity markets carry significant policy implications for investors in the energy sector.